Rodinný dům s ordinací lékaře - Štěpánková, Eva (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Bakalářská práce Rodinný dům s ordinací lékaře je zpracována formou projektové dokumentace obsahující všechny náležitosti dle platných předpisů. Navržený dům je umístěn na parcele č. 272/1 a 272/2 v obci Srch.

The bachelor project Family house with medical offices of physicians is compiled in a from of project documentation which comprises all the requisites required by current regulations. The designed house is placed on the sites numbered 272/1 and 272/2 in Srch.
family house with medical offices of Physicians
Keywords: Stavební projekt; technická zpráva; průvodní zpráva; souhrnná technická zpráva; situace; půdorys; řez; stropní konstrukce; plochá střecha; cihelné zdivo; betonový základ; schodiště; detail.; Construction project; technical report; accompanying report; totality technical report; situation; groud plan; cut; overhead construction; flat roof; brickwork masonry; concrete foundation; staircase; detail.